Distribution and diversity of emergent Banana bunchy top virus infecting banana and plantain in Cameroon, Central Africa - Ngatat, S.; Hanna, R.; Doumtsop Fotio, A.R.P.; Lienou, J.A.; Nanga, S.N.; Fotso Kaute, A.; Osundahunsi, B.; Fiaboe, K.; Ndemba, B.; Dossa, G.S.; Alabi, T.; Kumar, P.L. (Wiley, 2024)
Invasions of arthropod vectors and viruses are the main factors associated with emerging plant viral diseases. The presence of the Banana bunchy top virus (BBTV, genus Babuvirus), an aphid-transmitted virus responsible for the banana bunchy top disease (BBTD), was first confirmed in 2008 in the South region of Cameroon. This study reports on surveys over 14 years to determine the status of BBTV spread and virus diversity in Cameroon. A total of 544 fields extending through 81 districts in 7 regions were surveyed in 5 phases: (1) 2009–10, (2) 2012, (3) 2013–14, (4) 2016–17, and (5) 2022. BBTV was detected in 36 sites, all located in the Ambam district in the South region, with an incidence in the virus-affected fields ranging from 5% to 40%, with an average incidence of 14.8%. The findings indicate BBTV expansion from the location of first detection in 2008 to about 4–25 km in all directions, with the virus spread range of about 700 km2, as of the last survey in 2022. Phylogenetic analysis using complete nucleotide sequences of the BBTV-R and BBTV-S gene aligned Cameroon isolates with the sub-Saharan Africa subgroup of the Pacific-Indian Oceans (PIO) group of BBTV isolates, suggesting a likely virus invasion from neighbouring central African countries where BBTV presence had been reported in the 1980s. Knowledge of BBTV distribution provided through the detection and delimiting surveys has contributed to the efficient targeting of interventions to limit the expansion of an emerging virus threat to banana production in Cameroon.